A new iron supplement: The chelate of pig skin collagen peptide and Fe2+ can treat iron-deficiency anemia by modulating intestinal flora - Jiang, Shan; Dong, Weichao; Zhang, Zhen; Xu, Jing; Li, Haoran; Zhang, Jiayu; Dai, Long; Wang, Shaoping (Frontiers in Nutrition, 2022)
Iron deficiency anemia (IDA) is one of the most common nutritional diseases encountered all over the world. Nowadays, oral iron supplementation is still the mainstay of IDA treatment. In this study, a new iron nutritional supplement named pig skin collagen peptides ferrous chelates (PSCP-Fe) was prepared, and its structure was characterized by a series of analytical methods. The anti-IDA activity of PSCP-Fe was evaluated in low-Fe2+ diet-induced IDA in rats. 16S amplicon sequencing technology was then used to reveal the mechanism of PSCP-Fe against IDA. The results of amino acid analysis and fourier transform infrared (FTIR) showed that aspartic acid (Asp), arginine (Arg), histidine (His), glutamic acid (Glu), cystine (Cys), and lysine (Lys) residued in PSCP chelated readily with Fe2+ through their functional groups. The low-Fe2+ diet could significantly reduce the levels of red blood cells (RBC), hemoglobin (HGB), hematocrit (HCT), mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentrate (MCHC), serum ferritin (SF) and serum hepcidin (HEPC) (p<0.05), and significantly up-regulated the expression of serum transferrin receptor (TFR, p<0.05). Moreover, the IDA rats developed hepatocyte apoptosis and necrosis, Fe2+ loss, and injury. PSCP-Fe reversed the above situation, and its regulatory action was better than that of FeSO4. In addition, PSCP-Fe could significantly retrace the disturbed profile of gut microbiota in IDA rats (p<0.05) and significantly up-regulated the relative abundances of nine bacterial genus, including Lactobacillus, Alloprevotella, unclassified_of_Oscillospiraceae, and NK4A214_group (p<0.05). It could also downgrade the relative abundances of Subdoligranulum and Coriobacteriaceae_UCG-002 (p<0.05). The results of Spearman's correlation analysis and distance-based redundancy analysis (db-RDA) revealed that Subdoligranulum and Christensenellaceae_R-7_group may be potential microbial markers for effective PSCP-Fe action in the treatment of IDA. Overall, our results elucidate the interactions between gut bacteria and related cytokines and reveal the mechanisms underlying the anti-IDA effect of PSCP-Fe. They will thus provide a theoretical foundation for PSCP-Fe as a new iron nutritional supplement.